Muscle architecture and optimum angle of the knee flexors and extensors: A comparison between cyclists and australian rules football players - Brughelli, M.; Cronin, J.; Nosaka, K. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to investigate differences in optimum angle of peak torque (knee extensors and flexors) and muscle architecture (vastus lateralis) between 9 cyclists and 9 Australian Rules football (ARF) players. The angles of peak torque of the ARF players were significantly (p < 0.05) greater during knee extension (70.8 ± 3.5 vs. 66.6 ± 5.9°) and smaller during knee flexion (26.2 ± 2.9 vs. 32.3 ± 3.8°) compared with the cyclists. The ARF players had significantly (p < 0.05) smaller pennation angles (19.3 ± 2.0 vs. 24.9 ± 2.5°) and longer fascicle lengths (7.9 ± 0.7 vs. 6.2 ± 0.8 cm) in comparison with the cyclists. There were no significant differences between groups regarding muscle thickness or peak torque ratios between the quadriceps and hamstrings. Muscle architectural changes associated with resistance strength training need to be investigated so that the effects of training on architecture and functional performance can be determined.